THE EFFECT OF WORKING TIME AND NURSE ANXIETY LEVEL ON PATIENT SAFETY WITH EMOTIONAL INTELLIGENCE AS A MEDIATION VARIABLE AT DR SITANALA HOSPITAL - Herlina Herlina; Rokiah Kusumapradja; Hasyim (Jurnal Health Sains, 2022)
This study aims to determine the effect of working period and the level of anxiety of nurses on patient safety during the Covid-19 pandemic with the emotional intelligence of nurses as a mediating variable at RSUP DR Sitanala. The research methodology uses a quantitative approach and the analytical method used is the three box method and Path Analysis. Sampling technique using a total sampling of 190 respondents. The results of the study showed: the nurse's tenure has an influence on the emotional intelligence of nurses; nurses' anxiety level has an influence on nurses' emotional intelligence; nurses' tenure has an influence on patient safety; nurses' anxiety level has an influence on patient safety; nurses' emotional intelligence has an influence on patient safety; emotional intelligence variable is not a mediating variable between tenure and patient safety; emotional intelligence variable is not a mediating variable between the level of anxiety and patient safety. The findings of this study are that emotional intelligence is not a mediating variable between tenure and patient safety and emotional intelligence is not a mediating variable between anxiety levels and patient safety. Variable working period and level of anxiety have a significant effect on patient safety. The managerial implication of this research is an increase in religious activities to form emotional bonds in nurses so that they behave calmly and patiently, increase insight by strengthening training programs and refreshment of knowledge so that the application of patient safety goals can be handled properly and sustainably.